2011
DOI: 10.1021/jf200486t
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion Toxins Modify Phytopathogenic Fungus Physiology. A Possible Source of New Fungicides

Abstract: Seven toxins (F1ÀF7) were purified from Tityus discrepans scorpion venom on a C18 HPLC column. The compounds were fungitoxic on Macrophomina phaseolina. The molecular masses of F1ÀF7 were (Da) 1061. 1, 7328.8, 7288.3, 7268.5, 7104.6, 6924.6, and 6823.3, respectively. It is not known if F1 is a small peptide or some other kind of organic molecule. Compounds F2ÀF7 were peptides. The most potent was F7, with a minimal inhibition concentration of 0.4 μg/μL and a concentration for 50% inhibition of 0.13 μg/μL. Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In addition, our results suggest that some antifungal peptides, such as Ts1, may play their role by different modes-of-action, which might be related to uncharted receptors or other little-known channel types present on the fungus membrane. As a matter of fact, five toxins (F2 to F6) isolated from T. discrepans scorpion venom, with masses between 6,924.6 and 7328.8 Da, typical of scorpion toxins acting on sodium channels, showed antifungal effects against the phytopathogenic fungus Macrophomina phaseolina through three different ways: inhibiting fungus esterases and altering Na + membrane permeability and/or sterol biosynthesis (Joya et al, 2011). In this way, in-depth studies regarding Ts1 antifungal activity are necessary, in order to answer further questions, like its mechanism of action and its respective MIC or minimum effective concentration (MEC) quality control (QC) limits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results suggest that some antifungal peptides, such as Ts1, may play their role by different modes-of-action, which might be related to uncharted receptors or other little-known channel types present on the fungus membrane. As a matter of fact, five toxins (F2 to F6) isolated from T. discrepans scorpion venom, with masses between 6,924.6 and 7328.8 Da, typical of scorpion toxins acting on sodium channels, showed antifungal effects against the phytopathogenic fungus Macrophomina phaseolina through three different ways: inhibiting fungus esterases and altering Na + membrane permeability and/or sterol biosynthesis (Joya et al, 2011). In this way, in-depth studies regarding Ts1 antifungal activity are necessary, in order to answer further questions, like its mechanism of action and its respective MIC or minimum effective concentration (MEC) quality control (QC) limits.…”
Section: Discussionmentioning
confidence: 99%
“…In the Tityus discrepans venom HPLC fractionation, around 60 well-defined fractions were observed; those with the highest concentration were those belonging to retention times in the range of 20 to 25 min. Previous studies (19) of Tityus discrepans venom fractionated with HPLC (∼ 65 fractions) had shown that the peaks elute at similar retention times, where there were groups of compounds with similar size and activity.…”
Section: Discussionmentioning
confidence: 91%
“…Seven toxins (F1-F7), six of them peptides, were isolated and its antifungal effects on M. phaseolina characterized (Joya et al 2011). T. discrepans venom inhibits Macrophomina phaseolina growth in a concentration-dependent manner.…”
Section: Antifungic Active Toxinsmentioning
confidence: 99%
“…It is not known if F1 is a small peptide or some other kind of organic molecule (Joya et al 2011). It seems that interfering with sterol synthesis is the most important mechanism behind the fungicidal effect.…”
Section: Antifungic Active Toxinsmentioning
confidence: 99%